Odpowiedzi

2010-03-14T18:46:56+01:00
A)0,2* (-0,3) = - 0,06
-1,25*(-6,1)=7,625
-3,5*(-2/5)=1,4
-3 1/3 * 1 1/2 = - 10/5 * 3/2 = - 5
b) -6,2 : 1/5 = -31
2 3/4 : (-1/4)= -11
- 7 1/3 : (-0,5)= -22/5 * 2 = -2 1/5
0,25: (-0,05)= -5
c)
9
-8
81
-0,125
d)
1,44
- 8/27
1,21
1

i cała filozofia :)
Najlepsza Odpowiedź!
2010-03-14T18:55:09+01:00
A)
0,2×(-0,3)=-0,06
-1,25×(-6,1)=7,625
-3,5×(-2/5)=-3,5×(-o,4)=1,4
-3⅓×1½=-10/3×3/2=-5
b)
-6,2:⅕=-6,2×5=-31
2¾:(-¼)=2¾×(-4)=-11
-7⅓:(-0,5)=-7⅓×(-2)=14⅔
0,25:(-0,05)=-5
c)
(-3)²=9
(-2)³=-8
(-3)⁴=81
(-0,5)³=-0,125
d)
(-1,2)²=1,44
(-⅔)³=-8/27
(-1,1)²=1,21
(-1)²⁰=1